2021
DOI: 10.1002/wrna.1680
|View full text |Cite
|
Sign up to set email alerts
|

Biogenesis, characterization, and functions of mirtrons

Abstract: MicroRNAs (miRNAs) are major post-transcriptional regulators of gene expression. They base pair with the complementary target mRNA at the 3 0 UTR and modulate cellular processes by repressing the mRNA translation or degrading the mRNA. There are well-documented mechanisms of biogenesis of miRNA; however, a sizeable number of miRNAs are also produced by noncanonical pathways. Mirtrons represent a predominant class of non-canonical miRNAs. Mirtrons originate from intronic regions and are produced in a splicing-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 84 publications
0
34
0
Order By: Relevance
“…Upon splicing of introns from transcribed RNAs, the processing of pri-miRNAs and pre-miRNAs is preceded by linearization of intron lariat by debranching enzymes. While it was originally thought that mirtrons are Drosophila and C. elegans specific pathways further studies found mirtrons throughout the animal kingdom ( Siomi and Siomi, 2010 ; Salim et al, 2021 ). There are also miRNAs that are dicer-independent, but rely on the nuclear canonical machinery for miRNA biogenesis usually through cluster assistance, which will be discussed in detail in the next section ( Fang and Bartel, 2020 ; Shang et al, 2020 ).…”
Section: Mirna Biogenesis In Eukaryotesmentioning
confidence: 99%
“…Upon splicing of introns from transcribed RNAs, the processing of pri-miRNAs and pre-miRNAs is preceded by linearization of intron lariat by debranching enzymes. While it was originally thought that mirtrons are Drosophila and C. elegans specific pathways further studies found mirtrons throughout the animal kingdom ( Siomi and Siomi, 2010 ; Salim et al, 2021 ). There are also miRNAs that are dicer-independent, but rely on the nuclear canonical machinery for miRNA biogenesis usually through cluster assistance, which will be discussed in detail in the next section ( Fang and Bartel, 2020 ; Shang et al, 2020 ).…”
Section: Mirna Biogenesis In Eukaryotesmentioning
confidence: 99%
“…In contrast, an incomplete binding will result in mRNA translational repression. The non-canonical miRNAs are located in the intron region of the genes and are known as the mirtrons [18]. The splicing mechanism directly produces the stem-loop pre-miRNAs during the mRNA processing, thus bypassing the microprocessor complex of Drosha/DGCR8 processing.…”
Section: Micrornas and Hscsmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are small single-stranded RNAs. MiRNAs recognize miRNA response elements (MREs) on 3 UTR of mRNA and silence target genes through repressing mRNA translation or degrading the mRNA (Cheng et al, 2015;Salim et al, 2021). LncRNAs contain MREs and can use MREs to bind miRNAs.…”
Section: Introductionmentioning
confidence: 99%